Effectiveness of biologics in Australian patients with rheumatoid arthritis: a large observational study: REAL. Issue 10 (4th October 2018) - Nicholls, Dave; Barrett, Rina; Button, Peter; Truman, Matt; Bird, Paul; Roberts, Lynden; Tymms, Kathleen; Littlejohn, Geoffrey; Griffiths, Hedley
Abstract: Background: The comparative effectiveness of biologic treatment regimens in a real world Australian population is unknown. Aim: To assess the effectiveness of biological disease‐modifying anti‐rheumatic drugs (bDMARD) as monotherapy or in combination with methotrexate and/or other conventional DMARD (cDMARD) for the treatment of rheumatoid arthritis (RA). Methods: A retrospective, non‐interventional study was conducted that investigated the use of bDMARD in adult patients with RA in routine clinical practice. Data were extracted from the Optimising Patient Outcomes in Australian Rheumatology – Quality Use of Medicines Initiative database. Real‐world effectiveness was measured using the 28‐joint disease activity score (DAS28) and clinical disease activity index (CDAI) by treatment group at baseline, weeks 12 and 24. Results: A total of 2970 patients was included with a median (min–max) age of 60.0 (19.0–94.0) years and median (min–max) duration of RA before first bDMARD treatment of 6.0 (0.2–58.3) years. A total of 1177 patients received more than one bDMARD during the analysis period of 1 January 1997 to 15 August 2015. Patients had 4922 treatment 'episodes' (defined as a cycle of continuous individual bDMARD prescribing in a single patient). Patients received a mean (SD) of 1.7 (1.0) episodes of treatment with median (min–max) treatment duration of 0.7 (0–11.8) years; median treatment duration was higher with the first treatment episode. bDMARD were most commonly initiated in combination with methotrexate (73.9% of episodes) and least commonly as monotherapy (9.9% of episodes). Median (min–max) baseline DAS28 decreased from 5.3 (0–8.7) with the first bDMARD to 3.7 (0–8.8) with the second. Median baseline CDAI similarly decreased. Conclusions: Patients tended to persist longer on their first bDMARD treatment. bDMARD as monotherapy or in combination appear to be accepted treatment strategies in the real world.